Customer Behaviours towards Co-Branded Products of the Textile Industry - Grębosz, Magdalena; Otto, Jacek (Instytut Biopolimerów i Włókien Chemicznych (IBWCh) , Łódź, Polska, 2014)
Companies from the textile sector seek new methods of market expansion and increasing brand value. These methods include brand extension, brand licensing, acquisition of patent rights and co-branding, that is the strategy of double branding products when two distinct partner brand names are used on one product. Different studies show that the influence of co-branding on the behaviour of the consumer and their perception of products is high. For the authors, it was important to demonstrate the impact of co-branding on customer preferences concerning textile products for the example chosen. The aim of the research was to identify behaviours of consumers from the Lodz Voivodeship (Poland) when a co-branding strategy is used. As was proved in the study, the consumers give priority to a co-branded textile product in relation to a classic textile product. However, at the same time, those consumers do not give priority to a more expensive co-branded textile product in relation to the classic textile product. As was also proved in the study, the preferences of different groups of customers are not the same and the demographic, socio-professional and geographical characteristics of customers influence their behaviour towards the example of a co-branded textile product.
Keywords: textile product; co-branding; customer behaviour; brand; brand alliance